The Influence of Delivery Service Quality on J&T Express Customer Loyalty in North Jakarta During the Covid-19 Pandemic - Apriyani, Nur Dwi (Logistica : Journal of Logistic and Transportation, 2023)
The purpose of this study was to analyze and prove the effect of Delivery Service Quality on J&T Express Customer Loyalty in North Jakarta during the Covid-19 pandemic. This study uses an online survey method with a sample of 100 spread across the city of North Jakarta. The data analysis method used is simple linear regression test, T test, correlation coefficient test, and coefficient of determination test. The results obtained in the simple linear regression test is that the X value of 0.489 is positive. This shows that any increase in the quality of delivery service (X) will be followed by an increase in customer loyalty (Y) of 0.489. From the results of the t test with a t count of 10.281 > t table 1.98 with a significance of 0.000, it shows that the delivery service quality variable has a significant effect on customer loyalty for J&T express in North Jakarta during the Covid-19 pandemic. The results of the correlation coefficient with a correlation value of 0.720 can be concluded that the quality of delivery services with customer loyalty J&T express in North Jakarta during the Covid-19 pandemic has a strong relationship. Then the results of the coefficient of determination with an R Square value of 0.519 can be concluded that the effect of delivery service quality on J&T express customer loyalty in North Jakarta during the Covid-19 pandemic was 51.9% while 48.1% customer loyalty was influenced by other variables that not researched